2001
DOI: 10.1055/s-2001-18379
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotika und Phospholipidmetabolismus bei der Schizophrenie

Abstract: To date numerous in-vivo (31)P-MRS and in-vitro studies in schizophrenic patients have been able to demonstrate changes in their membrane phospholipid metabolism, which might be relevant for the cause and the therapeutic responsiveness of this disorder. Thus far, however, only limited studies exist regarding the specificity of these findings for schizophrenia and the effect of antipsychotic medication. The present study examined the composition of membrane phospholipids in platelets of 67 neuroleptic-free schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…This may be due to the different distribution of C-1 and C-2 positions of fatty acids with different lengths and saturation in glycerophosphate, leading to the different performance of the metabolite. Moreover, elevated TG levels may be the earliest and most sensitive indicator of the metabolic abnormalities associated with antipsychotics ( 26 ). Studies demonstrated the treatment with risperidone also elevated concentrations of TG ( 24 , 27 ), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the different distribution of C-1 and C-2 positions of fatty acids with different lengths and saturation in glycerophosphate, leading to the different performance of the metabolite. Moreover, elevated TG levels may be the earliest and most sensitive indicator of the metabolic abnormalities associated with antipsychotics ( 26 ). Studies demonstrated the treatment with risperidone also elevated concentrations of TG ( 24 , 27 ), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of lyso-PtdCho in schizophrenic patients are significantly reduced after 3 weeks of pharmacotherapy with haloperidol (Schmitt et al, 2001). This effect of haloperidol is caused by a dopamine-mediated decrease in PLA 2 activity.…”
Section: Fatty Acids and Glycerophospholipids In Schizophreniamentioning
confidence: 92%
“…Com isso, podem-se adotar tratamentos mais específicos de acordo com o prognóstico, visando a melhoria na qualidade de vida do paciente (Schneider et al, 2016). (Senaratne et al, 2009) e também um aumento de PC nas regiões corticais e subcorticais (Weber-Fahr et al, 2013), diminuição de PC no tálamo (Schmitt et al, 2001) e no lobo caudado (Yao et al, 2000) de pacientes com SCZ. Um estudo descreveu um aumento de AGs e PCs em pacientes com TB e SCZ em relação a controles saudáveis, tanto em tecido post mortem (substância branca e cinzenta) e glóbulos vermelhos (Schwarz et al, 2008).…”
Section: Discussionunclassified
“…As diferenças nos achados se mantêm em matrizes periféricas. McEvoy e colegas (2013) encontraram uma diminuição de AG, mas não de PC em plasma de pacientes com SCZ, já em plaquetas foi descrito uma diminuição de PC (Schmitt et al, 2001).…”
Section: Discussionunclassified